The Public Health Burden of Poor Quality of Life Following Coronary Angioplasty - Abdul Muttalib, Syed Nauman Raza, Syed Muhammad Zulfiqar Hyder Naqvi, Munir Ahmed Shaikh, Nazia Jameel, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
1) To determine quality of life in individuals following coronary angioplasty and,2) To determine socio-demographic factors associated with quality of life following coronaryangioplasty